Pseudonymization of PHI Items in German Clinical Reports. - Lohr, C.; Eder, E.; Hahn, U. (Stud Health Technol Inform, 2021)
We describe the adaptation of a non-clinical pseudonymization system, originally developed for a German email corpus, for clinical use. This tool replaces previously identified Protected Health Information (PHI) items as carriers of privacy-sensitive information (original names for people, organizations, places, etc.) with semantic type-conformant, yet, fictitious surrogates. We evaluate the generated substitutes for grammatical correctness, semantic and medical plausibility and find particularly low numbers of error instances (less than 1%) on all of these dimensions.
Keywords: *Confidentiality; Humans; *Privacy